The Influence of School Facilities and Social Support on Non-Academic Achievement: The Role of Study Club Extracurricular Mediation And Student Self-Efficacy - Wijayanti, Betha; Werdiningsih, Wilis (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
The non-academic achievement of students has not been the main focus of the school coaching strategy. Lack of facilities and low social support are considered to hinder student involvement and strengthen self-efficacy. This study aims to explore the role of extracurricular study clubs and self-efficacy as mediators in the influence of school facilities and social support on students' non-academic achievement. The survey method was used to collect data from 82 active students in the extracurricular study club of SMAN 2 Ponorogo through probability sampling techniques. The instrument used was a Likert scale questionnaire 1–4 which included 5 variables and 33 research constructs. Data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach to test 7 direct influences and 5 indirect influences. The results of the study showed that school facilities and social support had a positive and significant impact on students' non-academic achievement, both directly and indirectly through the mediation of self-efficacy and involvement in study clubs. Self-efficacy has been shown to have a strong mediating role in the relationship between social support and non-academic achievement. The implication of these findings is the importance of integrating extracurricular programs and confidence-building in educational strategies. This research makes a novel contribution through the simultaneous integration of physical environment variables, social support, psychological aspects, and student activities in a single PLS-SEM-based conceptual model.